Measurement of the Cellular Hemoglobin Concentration by Laser Scatter Method from Excessive Lipemic Sample: CASE REPORT - Gönel, Ataman; Koyuncu, Ismail (Combinatorial Chemistry & High Throughput Screening, 2019)
A 33-month old female child presented at a pediatric clinic with acute tonsillitis, and it was subsequently discovered that she had familial hyperlipidemia. Measurement of the patient’s whole blood tests was performed by a multiparameter automated hematology analyzer, the CELLDYN Ruby System® (Abbott, Lake Forest, USA) using venous blood extracted from a tube containing 3.0 mL of EDTA. Although her hematocrit levels were within normal limits, the hemoglobin (Hgb) level, mean corpuscular volume (MCH) and mean corpuscular Hgb concentration (MCHC) could not be determined using the spectrophotometric method. The results of these tests could not be measured when repeated using dilution. When the sample was left to rest for several minutes, it was observed to be excessively lipemic. The measurements were repeated using the Alinity HQ Analyzer® (Abbott), which determines Hgb concentration using laser scatter and spectrophotometry. Hgb cellular concentration was incorrectly measured as being 21.9 mg/dL using routine spectrophotometry (denoted by a flag indicating Hgb interference) and correctly found to be 10.8 mg/dL. Thus, in samples of excessive lipemia, Hgb, MCH, and MCHC levels cannot be measured accurately using spectrophotometry. Hematology analyzers that can measure cellular hemoglobin (cHGB) and average erythrocyte hemoglobin concentration (cHCM) by laser scatter method may be recommended when analyzing a blood sample that contains excessive lipemia.
Keywords: lipemia